A = { 1 ; 2 ; 3 ; 5 }
B = { 0 ; 2 ; 4 ; 6 }
C = { 1 ; 3 ; 6 ; 7 ; 8 ; 9 }
A ∪ B = { 0 ; 1 ; 2 ; 3 ; 4 ; 5 ; 6 }
B ∪ A = { 0 ; 1 ; 2 ; 3 ; 4 ; 5 ; 6 }
A ∩ B = { 2 }
( A ∪ B ) ∪ C = { 0 ; 1 ; 2 ; 3 ; 4 ; 5 ; 6 } ∪ { 1 ; 3 ; 6 ; 7 ; 8 ; 9 }
= { 0 ; 1 ; 2 ; 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 }
A ∪ ( B ∪ C ) = { 1 ; 2 ; 3 ; 5 } ∪ { 0 ; 1 ; 2 ; 3 ; 4 ; 6 ; 7 ; 8 ; 9 }
= { 0 ; 1 ; 2 ; 3 ; 4 ; 5 ; 6 ; 7 ; 8 ; 9 }
B ∩ A = { 2 }
A \ B = { 1 ; 3 ; 5 }
B \ A = { 0 ; 4 ; 6 }
( A \ B ) \ C = { 1 ; 3 ; 5 } \ { 1 ; 3 ; 6 ; 7 ; 8 ; 9 } = { 5 }
A \ ( B \ C ) = { 1 ; 2 ; 3 ; 5 } \ { 0 ; 2 ; 4 } = { 1 ; 3 ; 5 }